Effectiveness of Visual Imagery Versus Role-Based Strategies in Teaching Spelling to Learning Disabled Students - Craig Darch; Robert G. Simpson (Journal of Research in Rural Education, 1990)
The purpose of this study was to investigate the relative effectiveness of two approaches for teaching spelling. The subjects for this study were 28 upper elementary learning disabled students randomly assigned to ~ne of two treatment groups. One group of students was taught spelling with a visual imagery mnemonic, while the other was taught spelling with rule-based spelling strategies. Students were evaluated on three separate dependent measures: (a) three 10-item unit tests administered every 8 to 10 lessons, (b) a 25-item posttest consisting of randomly selected words from the entire instructional unit, and (c) The Test of Written Spelling, a standardized measure, administered etthe conclusion of instruction. The results of this spelling instruction study indicated that students taught with explicit rule-based strategies out-performed students presented with a visual imagery model on each of the dependent variables. The authors discuss the implication of these results for teachers of learning disabled students